Efektifitas Pembelajaran Matematika Menggunakan Model Learning Cycle 5e Berbantuan Media Komik Ditinjau Dari Gaya Belajar Siswa Kelas Vii SMP Muhammadiyah 1 Surakarta Tahun 2015/2016 - TYAS PUTRI UTAMI, CAHYANING, Rita P. Khotimah, S.Si.,M.Sc, Sri Rejeki, M.Pd.,M.Sc (2016)
This study aims at: (1) testing the effects of the 5E Learning Cycle model and 5E Learning Cycle -assisted comic media towards students' learning outcomes. (2) testing the effects of students' learning styles on students' learning outcomes. (3) testing the effects of interaction of learning models and students' learning styles on students' learning outcomes. This is a quantitative research with a quasi-experimental design. The population of this study is all students of 7th grade at SMP Muhammadiyah 1 Surakarta, and the samples are the students' of VIIA and VIIB. The data collection techniques used in this study are test, questionnaire and documentation. The data were analyzed using analysis of variance of two different cells with α = 5%. Based on the data analysis, it can be concluded that: (1) there is an effects of the 5E Learning Cycle model and 5E Learning Cycle -assisted comic media towards students' learning outcomes. Were students' learning outcomes with 5E Learning Cycle -assisted comic media are better than those who are treated by 5E Learning Cycle, (2) there is an effects of students' learning styles towards students' learning outcomes. Based on the test results further of post anava, it can be concluded that students' with visual learning styles have better learning outcomes than those with auditory and kinesthetic learning styles. The learning outcomes of students' with auditory learning styles are as well as the learning outcomes of students' with kinesthetic learning styles, and (3) there are no effects of interaction of learning models and learning styles of students towards students' learning outcomes.